Learning Strategies at Muhammadiyah 4 Gempol Junior High School During Pandemic Covid 19 - Risa Dwi Novita (International Consortium of Education and Culture Research Studies, 2021)
The study was intended to know the history and learning strategy during the covid-19 pandemic at the 4 muhammadiyah junior high school. Research methods are qualitative and analytical with data collection techniques through observation, interviews, written data, and school documentation. Based on research, the majority discussed the history of the school and described the muhammadiyah junior high strategy 4 majs in learning at the center of the covid-19 pandemic of learning activities during the pandemic of its learning, which was initially luring learning replaced with alternative learning, online learning. A procedure conducted by means of a video call (Google meet) in the presentation of the learning materials and the Google form exercise materials and also attendance attendance follow the online learning done in the whatsapp group. Teachers must understand competence in students, there are also factors that cause learning to be stencils such as students who are faced with problems not having adequate personal phones or Internet quotas as well as pandemic learning solutions that are supported at school as well as on the Internet in schools. It is hoped that they will maximize their teaching activities. Parents also play an important role, as they directly guide the student's learning and learning development, motivation is also important for the student to be diligent at home.